Respostas fisiológicas de genótipos de soja (Glycine max (L.) Merrill) em relação aos níveis de cobre - Schwalbert, Raíssa (2018)
Prolonged use of copper-based fungicides, that are used to control fungal diseases in vines, has led to the accumulation of Cu in the soil. This accumulation of Cu is observed in vineyards of several countries, including Brazil, such as the Campanha Gaúcha region vineyards. Soil mobilization increases organic matter oxidation and it increases copper availability, which in excess is toxic to young vine plants transplanted into soils of eradicated vineyards. Thus, after vineyard eradication, the using of annual crops, such as soybean, can phytoextract or phytostabilize Cu in the soil, reducing its toxicity to plants. In addition, soybean can fix atmospheric N2, increasing the N availability in soil, which is important in soils with low organic matter content. However, it is necessary to study soybean physiological responses to high Cu concentrations, and which soybean cultivars would be better adapted to this condition. The objective of the study was to evaluate the physiological responses of different soybean genotypes and the influence of soil mobilization on Cu phytotoxicity to the plants. Two studies were performed. Study 1 was conducted in hydroponic system and the treatments were composed of Cu concentrations (0.5, 20 and 40 μM Cu) and soybean cultivars (NA 5909 RG, DM 5958 RSF IPRO, M 6410 IPRO and DM 6563 RSF IPRO). 21 days after cultivation, leaf gas exchange was measured, SOD activity and H2O2 and TBARS concentrations in plants were evaluated. Dry matter of roots and dry matter of shoots, and Cu concentration in the tissues were obtained. Study 2 was performed in PVC tubes containing vineyard soil and natural field soil. Soil was collected with undisturbed and disturbed structure. Natural field soil was submitted to liming and fertilization. Seeds of soybean cultivars (DM 5958 RSF IPRO and M 6410 IPRO) were inoculated and sown in soil tubes. The same evaluations of study 1 plus the POD activity were performed. In both studies, plants grown at higher concentrations of Cu had lower dry mass production and lower photosynthetic rates, and they had higher Cu concentrations in tissues. In study 1, cultivar M 6410 IPRO was the least sensitive cultivar to Cu excess. This cultivar maintained the highest photosynthetic rate when exposed to higher Cu concentrations, and accumulated large concentrations of Cu in roots without reducing root dry mass production. It possibly have happened due to the higher SOD activity. On the other hand, the cultivar DM 5958 RSF IPRO drastically reduced its photosynthetic rate and its dry mass production in Cu excess. In study 2, for undisturbed soil structure, vineyard soil was more harmful to plant physiology than natural field soil. However, this response occurred in both soil types (vineyard and natural field), showing that the negative effect of tillage is not only related to the increase of soil availability Cu.